2012
DOI: 10.1002/jclp.21845
|View full text |Cite
|
Sign up to set email alerts
|

The PTSD Checklist—Civilian Version: Reliability, Validity, and Factor Structure in a Nonclinical Sample

Abstract: Overall, the PCL-C appears to be a valid and reliable measure of PTSD symptoms, even among nonclinical samples, and is superior to some alternative measures of PTSD. The factor structure among nonclinical samples may not reflect each of the PTSD symptom "clusters" (i.e., reexperiencing, avoidance/numbing, and hyperarousal).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
185
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(193 citation statements)
references
References 49 publications
8
185
0
Order By: Relevance
“…Future research should compare different samples in accordance with existing methods of establishing reliability (Conybeare, Behar, Solomon, Newman et al, 2012;Hunsley & Meyer, 2003;Joseph, Maltby, Wood et al;. Similarly, for clinical relevance,…”
Section: Future Researchmentioning
confidence: 94%
“…Future research should compare different samples in accordance with existing methods of establishing reliability (Conybeare, Behar, Solomon, Newman et al, 2012;Hunsley & Meyer, 2003;Joseph, Maltby, Wood et al;. Similarly, for clinical relevance,…”
Section: Future Researchmentioning
confidence: 94%
“…The study used the PCL-Civilian (PCL-C) version because it addresses the broadest range of possible events as the traumatic stressor. The PCL-C has demonstrated strong reliability and validity in multiple samples [17][18] and has good concurrent validity with the Clinician-Administered Posttraumatic Stress interview [19], the "gold standard" in diagnostic measurement of PTSD.…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%
“…This will create a small band of responses, which will lend to a single factor solution. The two factor solution is more interesting, as Conybeare et al (2012) demonstrated a two factor which differed with previous research, but said structure was explained by the authors as demonstrating the undergraduate response to stress as opposed to trauma. A clinical sample, therefore, should demonstrate a different factor structure than a non-clinical sample.…”
Section: Discussionmentioning
confidence: 62%
“…Despite being designed as a three factor structure, initial analysis by Conybeare et al (2012) found both a single factor solution based on the first eigenvalue, but a two factor solution based on the scree plot. In the suggested two-factor solution, one factor contained ten of the seventeen items, and accounted for 44.7% of the total variance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation